The level of knowledge about risk factors for cervical cancer and health-related behaviours of women from the area of the Świętokrzyskie Region - Lipińska, Anna M.; Karnia, Agnieszka; Włoch, Anna; Lipińska-Stańczak, Magdalena M.; Opuchlik, Anna M. (Medical Studies/Studia Medyczne, 2014)
Introduction : In the world cervical cancer is the second most common malignant tumour among women, as well as the second most common cause of death. Most often this disease develops in women who are between 35 and 59 years old, i.e. at the time when many women raise children and are active professionally. There is a close correlation between the incidence of cervical cancer and lifestyle and the risk factors associated with it. Aim of the research : Evaluation of the influence of knowledge about risk factors for cervical cancer on health-related behaviours of women from the area of the Świętokrzyskie Region. Material and methods: The research material was obtained on the basis of a survey. The study was conducted among 108 randomly selected women in the age range 20 to 60 years. Results: Based on the studies, a significant correlation between the women’s health-related behaviours and their age, level of knowledge, and awareness of belonging to the group at risk of cervical cancer was found. Conclusions: Among the respondents, older women showed more incorrect behaviours than younger women. It was also shown that the place of residence did not have an influence on health behaviour of the surveyed women. Respondents who participated in health education showed greater knowledge about the factors of cervical cancer than women not participating in the education. Women who were aware of belonging to the risk group for cervical cancer more often showed health-related behaviours.